Factor structure of Statistics Anxiety Rating Scale (STARs): EFA and CFA using Malaysian undergraduate psychology students - Abd Hamid, Harris Shah; Sulaiman, Muhamad Karimi (Springer, 2016)
Statistics courses are very important for social science students in understanding and analyzing research. Many students felt that statistics course is not applicable for undergraduate study except for pursuing postgraduate degrees. A study conducted in a Malaysian university found a negative relationship between anxiety and academic performance (Abd Hamid HS, Sulaiman MK, Int J Behav Sci 9(1):55–66, 2014a). However, the factor structure of the anxiety measure (STARs) had not been examined for Malaysian sample. This paper seeks to examine the factor structure of STARs which was reported to have six factors (Worth of Statistics, Interpretation Anxiety, Test and Class Anxiety, Computational Self-concept, Fear of Asking for Help, and Fear of Statistics Teachers) measured by 51 items. The scale was distributed to 132 undergraduate psychology students (26 males, 106 females) who took Psychological Statistics course. Exploratory factor analysis and confirmatory factor analysis were performed using SPSS and in AMOS respectively. The resulting model comprises five factors with 27 items. The six factors were not successfully replicated in the Malaysian sample; notably, the Interpretation Anxiety is missing. The findings are discussed in relation to the factor structure of another measure (Statistical Anxiety Scale) which was also tested in a Malaysian Sample (Abd Hamid HS, Sulaiman MK, Statistics anxiety, basic mathematics skills and academic performance among undergraduate psychology students. In Proceedings of the Asian conference on psychology & the behavioral sciences, 28–30 Mar 2014, Osaka, Japan, pp 452–463, 2014b).